Shifting Lu2SiO5 crystal to eutectic structure by laser floating zone. Issue 4 (April 2018) - Rey-García, F.; Sedrine, N. Ben; Fernandes, A.J.S.; Monteiro, T.; Costa, F.M.
Abstract: Starting from stoichiometric mixtures of lutetium and silicon oxides, Lu2 SiO5 (LSO) crystals to eutectic ceramic rods were obtained using the laser floating zone (LFZ) technique in air at growth rates ranging from 200 to 5 mm/h. The newly obtained eutectic is formed by Lu2 O3 fibrils and/or lamellae into a LSO matrix being its formation induced by a SiO2 evaporation process during the LFZ growth. Scanning electron microscopy (SEM) and Raman spectroscopy studies allowed observing how growth rate affects microstructural evolution, namely the transition from single crystal to eutectic. SEM observations show that the eutectics present alternated monophasic oxyorthosilicate regions with biphasic Lu2 SiO5 /Lu2 O3 ones identified by X-Ray diffraction as C2/c monoclinic Lu2 SiO5 and Ia 3 ¯ cubic lutetium oxide. While the luminescence phenomena were found to be only dependent on the excitation energy, a pronounced UV light-induced reversible photochromic effect was observed in the samples grown at slower rates.